Comparison of Volatile Composition between Alcoholic Bilberry Beverages Fermented with Non- Saccharomyces Yeasts and Dynamic Changes in Volatile Compounds during Fermentation - Liu Shuxun; Laaksonen Oskar; Marsol-Vall Alexis; Zhu Baoqing; Yang Baoru (American Chemical Society, 2022)
The profile of volatile compounds was investigated using headspace solid-phase microextraction coupled with gas chromatography–mass spectrometry (HS-SPME–GC–MS) during bilberry juice fermentation with nine non-Saccharomyces yeasts, including Pachysolen tannophilus, Metschnikowia pulcherrima, Hanseniaspora uvarum, Torulaspora delbrueckii, Zygosaccharomyces bailii, Schizosaccharomyces pombe, Lachancea thermotolerans, Issatchenkia orientalis, and Saccharomycodes ludwigii. Dynamic changes in volatile compounds were determined simultaneously with the development of ethanol concentration during fermentation. H. uvarum or I. orientalis produced more ethyl acetate than other yeast strains throughout fermentation, while fermentation with M. pulcherrima resulted in high accumulation of higher alcohols. S. pombe was associated with high productions of pentane-2,3-dione, 3-hydroxybutan-2-one, 2-methylbutanal, and 3-methylbutanal. Among the 59 volatile compounds detected, generally, higher alcohols and monoterpenes accumulated constantly and reached the maximum concentration at the middle or later fermentation stage, whereas aldehydes, ketones, and acetals accumulated first followed by a significant drop. The production and accumulation dynamics of metabolites were highly dependent on the yeast species and the developing ethanol content.